2017
DOI: 10.1021/acs.jafc.6b05501
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-Induced Leaf Chlorosis: Products of Chlorophyll Breakdown Found in Degreened Leaves of Phytoplasma-Infected Apple (Malus × domestica Borkh.) and Apricot (Prunus armeniaca L.) Trees Relate to the Pheophorbide a Oxygenase/Phyllobilin Pathway

Abstract: Phytoplasmoses such as apple proliferation (AP) and European stone fruit yellows (ESFY) cause severe economic losses in fruit production. A common symptom of both phytoplasma diseases is early yellowing or leaf chlorosis. Even though chlorosis is a well-studied symptom of biotic and abiotic stresses, its biochemical pathways are hardly known. In particular, in this context, a potential role of the senescence-related pheophorbide a oxygenase/phyllobilin (PaO/PB) pathway is elusive, which degrades chlorophyll (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…Significant new insights may be expected from in vivo analyses thanks to current methodological advances in the fields of mass spectrometry and of fluorescence‐spectroscopy . The specific natural availability of phyllobilins and of natural phyllobilin isomers in plant cells may signal fundamental endogenous cellular processes and/or responses to pathogens and external stress factors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant new insights may be expected from in vivo analyses thanks to current methodological advances in the fields of mass spectrometry and of fluorescence‐spectroscopy . The specific natural availability of phyllobilins and of natural phyllobilin isomers in plant cells may signal fundamental endogenous cellular processes and/or responses to pathogens and external stress factors …”
Section: Discussionmentioning
confidence: 99%
“…Significant new insights may be expected from in vivo analyses thanks to current methodological advances in the fields of mass spectrometry [43] [44] and of fluorescence-spectroscopy. [41][42] [45] The specific natural availability of phyllobilins and of natural phyllobilin isomers in plant cells may signal fundamental endogenous cellular processes and/or responses to pathogens [11] and external stress factors. [3] [40] The structures of phyllobilins are remarkably related to those of the heme-derived bilins, [1][13] [46] in spite of reflecting widely different pathways of the specific formation in the plants.…”
Section: Discussionmentioning
confidence: 99%
“…[32b, 36] The exceptional bcPBs in grapevine leaves may be surmised to play crucial (however,s till elusive) physiological roles, both in plants and in humans. Important experimentale videncea long these lines comesf rom the recently identified PBs in pathogenically de-greened apple and apricot leaves, [37] suggesting ar ole for PBs in the interaction of the plant host with bacterial or fungal pathogens, either as part of the plant's immune response [38] or the pathogen's virulence strategy.L ikewise, the possible health effects of such intriguing naturalp roducts as componentso f our daily nutrition are also an attractive, but stillu nexplored area of research. [2d] Complexm acrocyclic skeletons, like that of bcPBs, are af eature of physiologicallya ctive natural products, and are recognizeda se volutionary privileged structures in modern drug design approaches.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The colorless and non‐fluorescent phyllobilanes, or phylloleucobilins (PleBs), such as the NCC 11 from fall leaves of the deciduous Katsura tree ( Cercidiphyllum japonicum ), have been found accumulating in some senescent leaves in amounts corresponding to the Chls present in the corresponding green leaves . In many cases, however, the PleBs recovered corresponded to only 10–30 % of that amount, raising the question of the further fate of the Chl catabolites in the intact senescent leaves, suggesting decomposition of PleBs or their removal from their original environment by extracellular transport. Indeed, in support of the former possibility in the senescent leaves, yellow and pink colored Chl catabolites have been identified that arise via oxidation of the first formed phyllobilanes by a still hardly characterized ‘oxidative activity’ that is frequently found in leaves, as is evident by the occurrence of the products of the oxidation reaction, the PxBs.…”
Section: Phyllobilins Display a Rich Structural Varietymentioning
confidence: 99%
“…Recent advances in analytical methods tailored towards PBs have facilitated the detection of such natural products . In recent years, a range of fruit and vegetables were investigated in terms of their PB contents; as a consequence, various NCCs, DNCCs and YCCs were detected in apricots and plums, loquat fruit, lemons, olives, spinach, and broccoli; it is anticipated that many more are to follow.…”
Section: Beyond Chlorophyll Detoxification – Potential Bioactivities mentioning
confidence: 99%